Sorghum straw pellets: A dispatchable energy source for renewable energy transition - Bruno Rafael de Almeida Moreira; Damian Hine; Ian D. Godwin; Sudhir Yadav (Energy Conversion and Management: X)
The global transition to renewable energy is challenged by factors like intermittent solar and wind power, particularly in countries like Australia, where diverse landscapes and unique weather conditions add complexity. Biomass-to-solid fuels offer a reliable, dispatchable energy solution. This review synthesises the literature on sorghum biomass pelleting and evaluates its bioenergy potential, integrating data from the Sorghum Harvest Report and the Australian Biomass for Bioenergy Assessment. The pelleting process significantly enhances the energy density of sorghum straw from 3.7 GJ/m3 to 10.2 GJ/m3. If all available sorghum straw were converted into pellets, it could generate approximately 165.8 PJ/yr of bioenergy, representing 15.4% of Australia’s agricultural bioenergy potential (1077.5 PJ/yr). Sorghum-based pellets could contribute 43.5% to Australia’s bioelectricity potential (380.9 PJ/yr), surpassing other bioenergy sources, including cane bagasse (26.3%) and wood (23.4%). The use of sorghum straw pellets for bioenergy production has the potential to enable Australia to produce clean, reliable, and affordable energy, while providing new income opportunities for sorghum growers and contributing to rural economic development. This review also addresses sustainability concerns, such as the “fuel-food-feed” dilemma, proposing strategies for strategic resource allocation, the protection of marine ecosystems from agricultural runoff, and the repurposing of abandoned mining sites. By elucidating the availability and quality of sorghum straw, this study mitigates uncertainties that hinder the development of scalable biomass-to-pellet conversion technologies. The findings contribute to the broader discourse on achieving a sustainable, net-zero energy transition in Australia, with potential global implications for the development of decentralised, dispatchable renewable energy solutions.